061 The Study of the Effectiveness of Topical Testosterone and Estrogen for Urinary Tract Symptoms of GSM. (1st May 2022) - Ninomiya, N.; Sekiguchi, Y.
ABSTRACT: Introduction: Genitourinary Syndrome of Menopause (GSM) causes atrophic changes in the vulva and vagina due to a decrease in the amount of sex hormones with aging, causing unpleasant physical symptoms in the genital area. GSM symptoms are vulvar mucosa atrophy findings, vaginal dryness, lack of moisture during sexual intercourse, dyspareunia, frequent urination and urgency of urination, etc. Routine moisturizer use is recommended to prevent the progression of GSM symptoms, but the effect is insufficient from the perspective of mucosal improvement. In Europe and the United States, testosterone treatment is approved in addition to estrogen for GSM treatment, but it has not yet been approved in Japan. And its effect on GSM symptoms in Japanese women has not been investigated. Objective: The aim of this study is to examine the efficacy and safety of topical treatment with testosterone and estrogen for GSM. Methods: The survey was conducted from September 2019 to September 2020. Menopausal women with atrophy of the vulvar / vaginal mucosa and either urinary tract symptoms (frequent urination, urine leakage) or vaginal symptoms (vulvar pain, dryness) or sexual function symptoms (dyspareunia) was diagnosed as GSM and was included in the study. Patients with a history of surgery within 1 year and/or those with pelvic organ prolapse were excluded.An anatomical explanation of the vulva was given to the patient using a mirror during examination. Patients used topical hormone cream once daily for 1 month on the labia minora, external urethral meatus, and vestibule. The topical hormone cream contained 0.3% testosterone, 0.008% estradiol, and 0.003% ethinyl estradiol. The daily usage was 0.5 g.The effectiveness was evaluated as follows. The attending physician evaluated the vulvar moistness and the redness on a four-point scale. A Visual Analogue Scale (VAS) was used for contact pain. The Overactive bladder symptom score (OABSS) was used to assess urinary tract symptoms. All surveys were evaluated before and 1 month after use. Results: The survey was conducted on 30 patients aged 48 to 75 years (mean 58.3 years, median 58.5 years). The vulvar moistness was significantly improved. The redness was improved in the labia minora. No major changes were observed in vestibular region. Contact pain was significantly improved. OABSS improved significantly.Itching of the vulva was observed in 10%. Abnormal bleeding was observed in 10%. Nipple discomfort was noted in 5%. All side effects were not serious. Conclusions: Topical testosterone and estrogen are effective for GSM symptoms in Japanese women. Disclosure: Work supported by industry: no.